Brachytherapy of tongue carcinoma in a patient with difficult airway: anesthetic considerations - Ghaffar, Zainab Abdul; Chong, Soon Eu; Tan, Kok Leng; Appalanaido, Gokula Kumar; Musa, Muhamad Yusri; Hussin, Hasmah binti; Jusoh, Nurulhuda (Journal of Contemporary Brachytherapy, 2018)
The practice of brachytherapy in unresectable tongue carcinoma is gaining popularity. However, this procedure poses specific anesthetic challenges, particularly challenges of airway sharing and a higher rate of difficult airway. We report a 74-year-old chronic smoker, chronic alcoholic with history of stroke, who had undergone brachytherapy for tongue carcinoma. Apart from a huge tongue tumor, he had an epiglottic mass but refused elective tracheostomy. This had led to a few critical states throughout the process of treatment, including a metabolic crisis due to thiamine deficiency and difficult airway crisis. To our best knowledge, there have been no reported case on a patient with vocal cord mass undergoing tongue brachytherapy. We hope sharing of this experience may aid the management of similar patients in future.